Answer:
Tap A will take 2 hours and tap B will take 6 hours to fill the tank when turned on alone.
Step-by-step explanation:
Let tap B fills the pool alone in the time = x hours
So in one hour part of pool will be filled = ![\frac{1}{x}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%7D)
Another tap A when turned on, it takes time to fill the pool = x-5 hours
So in one hour part of the same pool filled = ![\frac{1}{x-5}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx-5%7D)
Now both the taps A and B are turned on then time taken to fill the pool = 3 hours.
Part of the pool filled in one hour by both the taps = ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
Now we form an equation
Part of pool filled in one hour by tap A + Part of pool filled in one hour by tap B = Part of pool filled in one hour by both the taps when turned on
![\frac{1}{(x-5)}+\frac{1}{x}=\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-5%29%7D%2B%5Cfrac%7B1%7D%7Bx%7D%3D%5Cfrac%7B1%7D%7B3%7D)
![\frac{x-5+1}{x(x-5)}=\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-5%2B1%7D%7Bx%28x-5%29%7D%3D%5Cfrac%7B1%7D%7B3%7D)
![\frac{x-4}{x(x-5)}=\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-4%7D%7Bx%28x-5%29%7D%3D%5Cfrac%7B1%7D%7B3%7D)
3(x - 4) = x(x - 5)
x² -5x = 3x - 12
x² - 8x + 12 = 0
x² - 6x - 2x + 12 = 0
x(x - 6) - 2(x - 6) = 0
(x -2)(x - 6) = 0
x = 2, 6 hours
We will take higher value of x as x = 6 hours for tap B.
Time taken by tap A = 6 - 4 = 2 hours.
Therefore, Tap A will take 2 hours and tap B will take 6 hours to fill the tank when turned on alone.
Answer:
(-1, -7)
Step-by-step explanation:
Used desmos, also, in these situations I believe you can take the number inside the brackets and make it negative and keep the number outside the same to find the vertex.
12 bags of mixed nuts for R2 each and 10 bags of dried fruit for R3 each
Given:
The statement is "-3 raised to the power 0".
To find:
The value of the given expression.
Solution:
We know that
raised to the power
can be written as
.
Any non zero number raised to the power 0 is always 1. It means,
, where
.
-3 raised to the power 0 ![=(-3)^0](https://tex.z-dn.net/?f=%3D%28-3%29%5E0)
![=1](https://tex.z-dn.net/?f=%3D1)
Therefore, the value of the given statement is 1.
1 Substitute
y
=
2
x
−
10
y=2x−10 into
y
=
4
x
−
8
y=4x−8.
2
x
−
10
=
4
x
−
8
2x−10=4x−8
2 Solve for
x
x in
2
x
−
10
=
4
x
−
8
2x−10=4x−8.
x
=
−
1
x=−1
3 Substitute
x
=
−
1
x=−1 into
y
=
2
x
−
10
y=2x−10.
y
=
−
12
y=−12
4 Therefore,
x
=
−
1
y
=
−
12
x=−1
y=−12